Acquiring Arabic As A Second Language Among Senior High School Students - Saleh, Zeiburhanus; Murtadlo, Nurul; Rosyidi, Abdul Wahab; Huda, Mokhammad Miftakhul; Hidayah, Eni Zulfa (Ijaz Arabi Journal of Arabic Learning, 2025)
Arabic language learning is widespread across schools, institutes, and universities. However, understanding the motivations and methods for learning Arabic as a second language is essential for effective language education. This study aims to explore Arabic language acquisition as a second language, specifically focusing on motivations and teaching methods. This research seeks to provide insights into enhancing Arabic language learning experiences by examining the support structures and instructional approaches. This study employs a qualitative research methodology, utilizing a case study approach. The study aims to uncover patterns and themes regarding Arabic language learning motivations and instructional strategies through systematic review and analysis of these materials. The research findings shed light on the significance of Arabic language acquisition as a second language in the context of support from school leaders and teachers and diverse teaching methods contributing to the effectiveness of Arabic language instruction. Additionally, initiatives such as language revitalization committees and language programs play a crucial role in promoting Arabic language learning. This study underscores the importance of understanding motivations and employing effective teaching methods to enhance Arabic language acquisition in educational settings.